Chronic cough in Vocal Cord Dysfunction: Description of a clinical entity. (July 2020) - Vertigan, Anne E.; Kapela, Sarah L.; Gibson, Peter G.
Abstract: Background and aim: Vocal Cord Dysfunction (VCD) and chronic cough (CC) are challenging conditions which lead to significant quality of life impairment. The underlying mechanisms are poorly understood, but laryngeal dysfunction may be common to both conditions. The aim of this study was to determine the characteristics of cough in VCD and whether patients with cough have coexisting VCD. Method: Participants included 51 patients with VCD and a comparison group of 39 patients with chronic cough that was refractory to medical treatment. Participants underwent a comprehensive assessment including questionnaires, laryngoscopy, cough frequency monitoring and voice testing. Results: Patients with VCD had significant cough morbidity with an increased cough frequency of 17.3 coughs/hour and reduced cough quality of life with mean Leicester Cough Questionnaire Score of 12.8. Breathing pattern abnormalities were also common in VCD and there was a strong correlation between the number of breathing pattern abnormalities and cough frequency (r = −0.827, p = 0.002). Cough measures were not significantly different between patients with VCD and those with CC. Moderate-severe PVFM was present in 69% of patients with CC. Abnormal vocal fold closure during phonation was also present in patients with chronic cough and was similar between the VCD (n = 40, 78.4%) and cough (n = 25, 64.1%) groups, p = 0.240. Conclusion: Cough is an important symptom in VCD. Patients presenting with chronic cough may have underlying VCD as a cause of their cough. Since cough and VCD symptoms co-occur clinicians need to consider cough when are treating VCD and VCD when treating chronic cough. Highlights: Chronic cough and vocal cord dysfunction might not be discrete entities. Vocal fold movement can be abnormal in chronic cough without respiratory symptoms. Cough quality of life is equally severe in chronic cough and vocal cord dysfunction.